Aspiration-mediated hydrogel micropatterning using rail-based open microfluidic devices for high-throughput 3D cell culture - Dohyun Park (Nature Portfolio, 2021)
Abstract Microfluidics offers promising methods for aligning cells in physiologically relevant configurations to recapitulate human organ functionality. Specifically, microstructures within microfluidic devices facilitate 3D cell culture by guiding hydrogel precursors containing cells. Conventional approaches utilize capillary forces of hydrogel precursors to guide fluid flow into desired areas of high wettability. These methods, however, require complicated fabrication processes and subtle loading protocols, thus limiting device throughput and experimental yield. Here, we present a swift and robust hydrogel patterning technique for 3D cell culture, where preloaded hydrogel solution in a microfluidic device is aspirated while only leaving a portion of the solution in desired channels. The device is designed such that differing critical capillary pressure conditions are established over the interfaces of the loaded hydrogel solution, which leads to controlled removal of the solution during aspiration. A proposed theoretical model of capillary pressure conditions provides physical insights to inform generalized design rules for device structures. We demonstrate formation of multiple, discontinuous hollow channels with a single aspiration. Then we test vasculogenic capacity of various cell types using a microfluidic device obtained by our technique to illustrate its capabilities as a viable micro-manufacturing scheme for high-throughput cellular co-culture.